Gender and race trends in academic rank of dermatologists at top U.S. institutions: A cross-sectional study - Claire Stewart, B.A; Shari R. Lipner, M.D., Ph.D (Wolters Kluwer, 2020)
Background: Despite growth in the proportion of women and underrepresented minorities in the dermatology workforce, gender and racial differences persist. Objective: This study sought to analyze the differences in academic rank between genders and races while controlling for achievement indicators. Methods: Data from 15 institutions, selected based on residency program rankings, were analyzed. Results: Women were well-represented as assistant professors (60.7% vs. 37.6% of men; p < .001) and underrepresented as full professors (17.0% vs. 37.6%; p < .001). However, in a multivariable analysis controlling for career duration, publications per year, National Institutes of Health funding, and PhD degrees, neither gender (adjusted odds ratio [aOR]: 1.01; confidence interval [CI], 0.55-2.73) nor race (aOR: 1.24; CI, 0.53-2.92) was associated with a higher academic rank. Career duration (aOR: 1.24; CI, 1.18-1.30), publications per year (aOR: 1.48; CI, 1.28-1.74), and National Institutes of Health research funding (aOR: 4.29; CI, 1.53-12.88) were predictive of higher academic rank. Conclusion: Our findings confirm that for equal levels of achievement, men and women are promoted similarly in dermatology, yet reasons for disparity in research output and funding for women and minority dermatologists need further study.